Urban Seniors in Finland in the year 2035 : Horizon scanning of inclusion and volunteering in the future - Seikkula, Tiina (My University, 2023)
The study explores the future of the volunteering and inclusion among seniors in urban areas in Finland. The research aim is then to examine elements of inclusion and roles given volunteering in the lives of urban seniors in the future. The thesis aims to offer views into the futures of urban seniors, reaching its timescale to the year 2035. Behind this interest is the megatrend of aging which is expected to have huge structural and mental effects in Finnish society. Methodologically the study draws on horizon scanning. The horizon scanning is used to identify phenomena potentially impacting in the lives of urban seniors in the future, and the results from this are compared with previous studies observations on the lives of urban seniors. The distinct elements of lives of urban seniors are discussed within framework identifying the role of welfare system, age-friendly movement and anti-ageing innovations. However, the main focus is on inclusion and volunteering, constituting the primary research objective of the study. The applied horizon scanning is based on desk research, and through it the study aims to provide a broader view on the issues examined in the thesis. The thesis offers rudimentary material for the development work of different NGOs and organisations, whose agenda has to do with the future of urban seniors in Finland. By introducing a variety of perspectives to urbanisation and aging as well as to inclusion and volunteering, the study provides insights to grasp alternative developments that shape the future lives of urban seniors. The study suggests that inclusion will continue to be a very important part of the well-being of seniors. The elements of inclusion are built regardless of age, based on everyone's own starting points and resources. In the future, digital accessibility, age-friendly environment support building inclusion. In addition, the study identified volunteering as a means to produce well-being and inclusion. This is despite of the fact that the forms of volunteering are developing towards a project-type commitment while also field of organisations changing. Finally, the thesis also addresses some weak signals, which can play a significant role in the future, mentioned in the analysed future programmes. Through this analysis the thesis suggest that future of ageing and inter-generational issues should be discussed more thoroughly. As ageing is inevitable anticipation for ageing is needed throughout the life-cycle. Successful aging creates an opportunity to feel inclusion also in the future. The thesis concludes that planning alternative futures related to ageing should be done by individuals, organisations and societies.

Tämän tutkimuksen tarkoituksena on selvittää suomalaisten kaupunkiseutujen ikäihmisten vapaaehtoistyön ja osallisuuden tulevaisuutta. Tavoitteena on siten tarkastella osallisuuden elementtejä ja sitä, mikä on vapaaehtoistyön rooli urbaanien ikäihmisten elämässä tulevaisuudessa. Opinnäytetyön tavoitteena on tarjota näkemyksiä urbaanien senioreiden tulevaisuudesta vuoteen 2035 mennessä. Tämän kiinnostuksen taustalla on ikääntymisen megatrendi, jolla odotetaan olevan valtavia rakenteellisia ja henkisiä vaikutuksia suomalaisessa yhteiskunnassa. Metodologisesti työ perustuu horizon scanning -menetelmään. Horisontin skannauksen avulla etsitään yksityiskohtia ilmiöistä, jotka saattavat vaikuttaa kaupunkilaisten seniorien elämään tulevaisuudessa. Pääpaino on tiedon keräämisessä kaupunkilaisten ikäihmisten elämästä aiemmista tutkimuksista. Horisontin skannaus havaitsee erilaisia tulevaisuuden merkkejä. Siksi ilmiöitä selkeytetään ja verrataan eri organisaatioiden (YK, EU ja STM) tulevaisuussuunnitelmiin. Urbaanien ikäihmisten elämän eri elementtejä käsitellään viitekehyksessä, jossa tunnistetaan hyvinvointijärjestelmän, ikäystävällisen suuntauksen ja anti-ageing innovaatioiden rooli. Osallisuutta ja vapaaehtoistyötä korostetaan enemmän, koska ne ovat tämän tutkimuksen keskeiset kiinnostuksen kohteet. Horisontin skannaus perustuu usein työpöytätutkimukseen, mikä auttaa kehittämään kokonaiskuvaa tutkittavien asioiden taustalla. Tämä tutkimus tarjoaa perusaineistoa ennakointityöhön erilaisille kansalaisjärjestöille, jotka ovat mukana kaupunkien ikäihmisten tulevaisuudessa. Tämä tutkimus avaa keskusteluja ja siten aineksia erilaisiin ja paikallisesti mahdollisiin kaupunkien tulevaisuuksiin. Suunnitelmat vaihtoehtoisista tulevaisuuksista voitaisiin tehdä seniorien toimesta tai heidän kanssaan. Osallisuus on jatkossakin erittäin tärkeä osa ikäihmisten hyvinvointia. Osallisuuden elementit rakentuvat iästä riippumatta, jokaisen omien lähtökohtien ja voimavarojen pohjalta. Tulevaisuudessa digitaalinen saavutettavuus ja ikäystävällinen ympäristö tukevat osallisuuden rakentamista. Vapaaehtoistyön tulevaisuuden rooli on tuottaa hyvinvointia ja osallisuutta. Tulevaisuudessa vapaaehtoistyö muuttuu projektityyppiseksi sitoutumiseksi ja organisaatiokenttä muuttuu. Kiinteä kytkentä yhteiskunnan rakenteisiin irrottaa kansalaisyhteiskunnan idean ja arvon vapaaehtoistyöstä. Ikäohjelmissa mainittiin heikkoja signaaleja, joilla voi olla merkittävä rooli tulevaisuudessa. Ikääntymisen tulevaisuudesta ja sukupolvien välisistä kysymyksistä olisi keskusteltava. Ikääntymiseen varautumista tarvitaan kaikilla elämän osa-alueilla. Ikääntyminen on väistämätöntä. Onnistunut ikääntyminen luo mahdollisuuden tuntea osallisuutta myös tulevaisuudessa. Ikääntymiseen liittyvien vaihtoehtoisten tulevaisuuksien suunnittelua tulisi tehdä yksilöiden, organisaatioiden ja yhteiskuntien toimesta.
Keywords: senior, Finland, inclusion, volunteering, horizon scanning